Pola Asuh Orang Tua, Aktifitas Fisik Remaja dengan Status Nutrisi - Angelina, Ria (Sekolah Tinggi Ilmu Kesehatan YARSI Mataram, 2023)
Nutrients are chemical substances in food that are used by the body for growth and development. Parenting is one of the factors that are closely related to growth and development, one of which is food as a source of nutrition. The proportion of the population based on the age group of 13-18 years regarding energy adequacy in 2014 that experienced energy adequacy was very less, there was 52.5%, 32.5% less normal 12.2% more than 5.0%. Adolescence becomes more concentrated on the physical self which must be supported by good nutrition, so that adolescents can carry out strong and healthy activities to support their daily learning processes, where the need for parents to fulfill balanced nutrition for adolescents. This study aims to analyze the relationship between parenting and physical activity with the nutritional status of adolescents. The population in this study were teenagers, with the number of research samples using the sampling technique obtained by 69 respondents. The analysis used is univariate analysis using frequency distribution and bivariate analysis using chi square. The results of the study obtained p value 0.00 <0.05, there was a relationship between parenting and nutritional status, and p value 0.00 <0.05, namely there was a relationship between physical activity and adolescent nutritional status. Suggestions for nurses need to monitor nutritional status in schools, as well as programs to make reports on nutritional status by making daily menus, and increasing physical activity with movement exercises/gymnastics. For the next researcher, it is important to examine what factors are related to adolescent physical activity and adolescent nutritional status.